Psychometric Properties of the Couple Time Sharing Scale in an Argentine Sample (Revista de Psicología, 2023)
Shared time is understood as the availability of time towards the other member of the couple and the use that is given to it. The objective of the work was to evaluate the psychometric properties of the Couple Time Sharing Scale (TCP) in a sample from Entre Ríos, Argentina. Internal consistency was evaluated through Cronbach's Alpha analysis. To confirm internal validity, an Exploratory Factor Analysis was carried out. Convergent validity with satisfaction in the couple was evaluated through Pearson's r Correlation Analysis. The results allow us to affirm that the version obtained presents appropriate reliability and validity properties, and may be a relevant instrument to be administered in the Argentine population.
Keywords: Shared time; Couple; Satisfaction; Positive psychology; Scale